Development of a Chemically Defined Medium for in vitro Expansion of Primary Bovine Satellite Cells - Kolkmann, Anna M.; Van Essen, Anon; Post, Mark J.; Moutsatsou, Panagiota (Frontiers in Bioengineering and Biotechnology, 2022)
The use of fetal bovine serum (FBS) in animal cell culture media is widely spread since it provides a broad spectrum of molecules that are known to support cell attachment and growth. However, the harvest and collection procedures of FBS raise ethical concerns and serum is an ill-defined and expensive component. This is especially problematic when it comes to regulatory approval for food applications like cultured meat. The aim of this study is to develop a chemically defined, cost efficient serum-free and animal-free medium that supports the attachment and expansion of bovine myoblasts while maintaining their differentiation capacity. Bovine satellite cells were harvested and isolated from a fresh sample of skeletal muscle tissue and cultured in planar systems. The efficacy of the tested formulations was assessed with metabolic assays and cell counting techniques. Optical microscopy was used to observe cellular morphology and statistical analysis was applied. Based on a comprehensive literature analysis, a defined serum-free medium (SFM) composition was developed consisting of DMEM/F12 as basal medium, supplemented with L-ascorbic acid 2-phosphate, fibronectin, hydrocortisone, GlutaMAX™, albumin, ITS-X, hIL-6, α-linolenic acid and growth factors such as FGF-2, VEGF, IGF-1, HGF and PDGF-BB. To our knowledge, this is the first defined serum-free & animal free medium formulation specific for bovine myoblasts to date. We conclude that the SFM formulation supported exponential cell growth up to 97% of the serum – containing golden standard growth medium. All reagents used in this study are chemically defined.